A phase 1 study of the pan‐bromodomain and extraterminal inhibitor mivebresib (ABBV‐075) alone or in combination with venetoclax in patients with relapsed/refractory acute myeloid leukemia. Issue 16 (2nd May 2021) - Borthakur, Gautam; Odenike, Olatoyosi; Aldoss, Ibrahim; Rizzieri, David A.; Prebet, Thomas; Chen, Chris; Popovic, Relja; Modi, Dimple A.; Joshi, Rujuta H.; Wolff, Johannes E.; Jonas, Brian A.
Abstract : Background: Acute myeloid leukemia (AML) is a heterogenous malignancy driven by genetic and epigenetic factors. Inhibition of bromodomain and extraterminal (BET) proteins, epigenetic readers that play pivotal roles in the regulation of genes relevant to cancer pathogenesis, constitutes a novel AML treatment approach. Methods: In this first‐in‐human study of the pan‐BET inhibitor mivebresib as monotherapy (MIV‐mono) or in combination with venetoclax (MIV‐Ven), the safety profile, efficacy, and pharmacodynamics of mivebresib were determined in patients with relapsed/refractory AML (ClinicalTrials.gov identifier NCT02391480). Mivebresib was administered at 3 monotherapy dose levels (1.5, 2.0, or 2.5 mg) or in combination with venetoclax (400 or 800 mg). Results: Forty‐four patients started treatment: of 19 who started MIV‐mono, 5 went on to receive MIV‐Ven combination therapy after disease progression and a washout period. Twenty‐five patients started MIV‐Ven, resulting in a total of 30 patients treated with the combination. The most common mivebresib‐related treatment‐emergent adverse events were dysgeusia (74%), decreased appetite (42%), and diarrhea (42%) in the MIV‐mono group and decreased appetite (44%), vomiting (44%), and nausea (40%) in the MIV‐Ven group. Serious adverse events occurred in 14 patients (74%) who received MIV‐mono and in 22 patients (88%) who received MIV‐Ven. In the MIV‐mono group, responses were complete remission with incomplete blood count recovery in 1 patient and resistant disease in 15 patients. In the MIV‐Ven group, responses were complete remission in 2 patients, partial remission in 2 patients, morphologic leukemia‐free state in 2 patients, resistant disease in 12 patients, and aplasia in 1 patient. The pharmacodynamic effects of mivebresib were proportional to dose and drug exposure. Conclusions: Mivebresib was tolerated and showed antileukemic effects as monotherapy and in combination with venetoclax in patients with relapsed/refractory AML. Lay Summary: Mivebresib is a novel drug that influences the way cancer cells read genetic information. Mivebresib was tested together with venetoclax in patients with acute myeloid leukemia after standard medicines failed and the disease returned, or when standard medicine was unavailable. Adverse effects were described for different drug doses, and the dose that is tolerable was determined. In some patients, their leukemia improved for some time. More studies are necessary to determine whether mivebresib can be used to treat acute myeloid leukemia. Abstract : Mivebresib is tolerable and produces antileukemic effects as monotherapy and when combined with venetoclax in patients who have relapsed/refractory acute myeloid leukemia. Mivebresib also demonstrates a statistically significant dose‐dependent correlation between biomarker modulation and drug exposure.